Preferred positions for solo, duet, and quartet performers on stage in concert halls: In situ experiment with acoustic measurements. (November 2015) - Jeon, Jin Yong; Kim, Young Sun; Lim, Hansol; Cabrera, Densil
Abstract: The relationship between the objective characteristics of the stage performance environment and the subjective impressions of musicians was investigated in two chamber halls with different architectural characteristics. In order to characterize the stage, acoustical and visual parameters were measured and representative parameters were derived using principle components analysis. Stage support (ST) parameters, such as STEarly and STLate, were selected as main factors and measured at various measurement positions on the stage according to ISO 3382-1. Subjective evaluations were also conducted to find the musicians' subjective impressions of acoustic conditions, including overall quality in solo, duet, and quartet performances during in-situ performances at six positions on the stage. Subjective evaluations indicate that the stage front is the most preferred position for musicians and the differences in response to the positions were less significant for a solo performance compared to those for duet and quartet performances. The relationship between ST parameters and subjective impressions was investigated using correlation and multiple regression analyses. From the results, it was found that the soloists' preferences increased but the quartet performers' preferences decreased under conditions with stronger early and late reflections. Highlights: Stage support parameters and subjective impressions were investigated in two halls. In solo performance, early and late reflections enhance musicians' preference. In quartet performance, early reflections interfere with musicians' ensembles. Stage support parameters should apply according to the performance type.